Morphological and Phenological Attributes of Chickpea (Cicer arietinum L.) Affected by Different Growing Conditions, Zeolite and Nitrogen Applications - Engin Takıl; Nihal Kayan (Turkish Journal of Agriculture: Food Science and Technology)
The present study investigated the effects of two different zeolite applications and different nitrogen-based fertilizers on chickpea’s yield and yield components in dry and irrigated conditions. The field experiment was conducted during 2019 and 2020 in the experimental area of the Faculty of Agriculture, Eskisehir Osmangazi University, Eskisehir, Türkiye. The experimental design was a split-split plot with four replicates. The main plots were grown under dry-irrigated conditions. At the same time, subplots received zeolite applications (zeolite+- zeolite-), and sub-sub plots received nitrogen applications [control, traditional, chemical, farmyard manure, and Isabion, (an animal collagen-derived biostimulant)]. The experiment found that irrigation caused a delay in phenological characters but had a favorable impact on morphological characters and yield. The effect of zeolite applications was different in the first and second years of the experiments for the investigated characters. In the first year, the application of zeolite had a significant impact on grain yield, but there was no discernible effect in the second year. The experiment demonstrated that both chemical fertilizer and farmyard manure positively impacted phenological and morphological characteristics. In both years, the farmyard manure plots produced the highest grain yield. Farmers in Türkiye are advised to apply nitrogen to their crops as the profitability of chickpeas has risen in recent years. If the high cost of farmyard manure renders its use impracticable, farmers can opt for chemical fertilizer as an alternative.